PENGARUH PELATIHAN INOVASI DAN PRODUKTIVITAS TERHADAP KINERJA MELALUI LINGKUNGAN KERJA FISIK - Muhamad Nasrip; Novi Anggreini (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The purpose of this study is to examine the effect of innovative training and productivity on performance through the physical work environment. Using data from a survey of 35 employees, a path analysis was performed using the PLS 3 program to evaluate the hypothesis.  According to the analysis findings, performance is positively and statistically significantly impacted by innovative training and productivity. Employee performance was also found to be positively and significantly impacted by the physical work environment. Furthermore, the study findings suggest that productivity and innovative training have a big impact on the actual workspace. Additional mediation tests support the significance of the physical work environment. The relationship between productivity and performance, and the relationship between innovative training and performance, were considerably mediated by the physical work environment.  According to this study, in order to attain the best possible staff performance, firms must combine innovative training and productivity enhancement with physical work environment upgrades. Therefore, it is recommended that management offer relevant training, create a comfortable workplace, and provide support.  Future studies should look at moderating variables, including corporate culture or technology, as well as non-physical elements.